DIFFERENCES IN MOTOR SKILLS OF SELECTED AND NONSELECTED GROUP OF CHILDREN IN ARTISTIC GYMNASTICS IN THE CONTEXT OF THEIR MOTOR DEVELOPMENT (Kinesiology, 2019)
Main purpose of this paper was to find differences in motor skill level between selected and non-selected group of children in artistic gymnastics. Artistic gymnastics is one of the sports that is frequently put into a negative context because of early specialization of children, while at the same time it is considered to be basic, fundamental sport. Thirty-one child (age 5.59 ± 0.77) participated in this study. The data was collected using Test of Gross Motor Development – Second Edition (TGMD-2). One-way ANOVA and Bonferroni post-hoc test were used to determine the differences in motor skills in children. The results show differences in locomotor skills between selected and non-selected children gymnasts (p